2015
DOI: 10.1063/1.4918361
|View full text |Cite
|
Sign up to set email alerts
|

The Dirac point electron in zero-gravity Kerr–Newman spacetime

Abstract: Dirac's wave equation for a point electron in the topologically nontrivial maximal analytically extended electromagnetic Kerr-Newman spacetime is studied in a limit G → 0, where G is Newton's constant of universal gravitation. The following results are obtained: the formal Dirac Hamiltonian on the static spacelike slices is essentially self-adjoint; the spectrum of the self-adjoint extension is symmetric about zero, featuring a continuum with a gap about zero that, under two smallness conditions, contains a po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…Using the Chandrasekhar-Page-Toop separation of variables, and an argument of Weidmann [50], in [31] we prove:…”
Section: The Continuous Spectrum Ofĥmentioning
confidence: 97%
See 3 more Smart Citations
“…Using the Chandrasekhar-Page-Toop separation of variables, and an argument of Weidmann [50], in [31] we prove:…”
Section: The Continuous Spectrum Ofĥmentioning
confidence: 97%
“…Note that H is not equivalent to L 2 (Z) whose inner product has the identity matrix in place ofM . We are finally ready to list our main results which are proved in [31].…”
Section: A Hilbert Space Forĥmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the metric of zGKN and the electromagnetic field corresponding to it are well known, it is easy to formulate the quantum dynamics of a test electron placed in the vicinity of the ring singularity by studying the Dirac equation on the zGKN background. This task was carried out in [17], where it was shown, using techniques developed in [2,26], that the pertinent Dirac Hamiltonian is essentially self-adjoint and its essential spectrum is the same as the standard Dirac operator on Minkowski space. We further showed that its discrete spectrum is nonempty, provided the radius of the ring is small enough.…”
Section: Point Particle In Zero-gravity Kerr-newmann Spacetimementioning
confidence: 99%